Efficient Education Environment at University Level - Selmeci, A.; Orosz, T. (Acta Technica Jaurinensis, 2014)
Technology changes in the last twenty years accelerated and sped up the life around the World. Nowadays new generations arise having no paper based textual information, technology based and thinking young people are coming to the universities in the next years. The universities and the education systems are currently not prepared to handle the different thinking, living, learning mechanism of them. Our study highlights the possible problems and show a way how to cover in short time the gap and offers new directions as well.